A Tangle of Spells - Harrison, Michelle (London Simon & Schuster, 2021)
It should have been a fresh start for the Widdershins sisters, Betty, Fliss and Charlie, who have left the misty gloom of Crowstone for a new life in the pretty village of Pendlewick. But all is not as it seems and as one of their own begins to slip away from them, the sisters find themselves in a race against time to break a dark magic that has cast a spell over the village
Keywords: Magic -- Adventure stories -- Children's stories -- Fairy tales -- Fantasy